(untitled) (Research, Society and Development, 2021)
Objective: Sleep bruxism (SB) is considered masticatory muscle activities that occur during sleep, which can interfere in stomatognathic system function. When treatment occurs earlier, most of the signs and symptoms can be prevented. However, there are few studies about treatment in early ages. Thus, the present study aimed to evaluate muscle activity and bite force changes after massage therapy (MT) and the use of occlusal splints (OST) for children with SB. Methodology: Forty-eight children were divided into 4 groups after SB diagnosis, according to the American Academy of Sleep Medicine’s criteria: Group 1–without bruxism; Group 2–SB, MT treated; Group 3–SB, OST treated for 30 days; Group 4–SB, not treated. Children were submitted to initial and final bite force (BF) evaluations and muscular activity, using a digital dynamometer and BiteStrip®, respectively. The results were computed and statistical analysis performed using SPSS 20.0 program, with a significant level of 95% (p ≤ 0.05). Results: Significant differences were statistically found in muscle activity in Group 3 (p = 0.003) and BF in both Groups 2 (p = 0.001) and 3 (p = 0.007). Conclusion: Results indicate that the use of OST led to a reduction in muscle activity and increase on BF in children with SB, whereas MT did not alter muscle activity, but provided an increase on BF in these children.